In vitro and in vivo characterization of antibacterial activity and biocompatibility: A study on silver-containing phosphonate monolayers on titanium. (15th March 2015) - Tîlmaciu, Carmen-Mihaela; Mathieu, Marc; Lavigne, Jean-Philippe; Toupet, Karine; Guerrero, Gilles; Ponche, Arnaud; Amalric, Julien; Noël, Danièle; Mutin, P. Hubert
Graphical abstract: Abstract: Infections associated with implanted medical devices are a major cause of nosocomial infections, with serious medical and economic repercussions. A variety of silver-containing coatings have been proposed to decrease the risk of infection by hindering bacterial adhesion and biofilm formation. However, the therapeutic range of silver is relatively narrow and it is important to minimize the amount of silver in the coatings, in order to keep sufficient antibacterial activity without inducing cytotoxicity. In this study, the antibacterial efficiency and biocompatibility of nanocoatings with minimal silver loading (∼0.65 nmol cm −2 ) was evaluated in vitro and in vivo. Titanium substrates were coated by grafting mercaptododecylphosphonic acid (MDPA) monolayers followed by post-reaction with AgNO3 . The MDPA/AgNO3 nanocoatings significantly inhibited Escherichia coli and Staphylococcus epidermidis adhesion and biofilm formation in vitro, while allowing attachment and proliferation of MC3T3-E1 preosteoblasts. Moreover, osteogenic differentiation of MC3T3 cells and murine mesenchymal stem cells was not affected by the nanocoatings. Sterilization by ethylene oxide did not alter the antibacterial activity and biocompatibility of the nanocoatings. After subcutaneous implantation of the materials in mice, we demonstrated that MDPA/AgNO3 nanocoatings exhibit significant antibacterial activity and excellent biocompatibility, both in vitro and in vivo, after postoperative seeding with S. epidermidis . These results confirm the interest of coating strategies involving subnanomolar amounts of silver exposed at the extreme surface for preventing bacterial adhesion and biofilm formation on metallic or ceramic medical devices without compromising their biocompatibility.